2018
DOI: 10.1136/bmjopen-2018-021748
|View full text |Cite
|
Sign up to set email alerts
|

Can the STarT Back Tool predict health-related quality of life and work ability after an acute/subacute episode with back or neck pain? A psychometric validation study in primary care

Abstract: ObjectivesThe predictive ability of the STarT Back Tool (SBT) has not yet been examined among acute/subacute back and/or neck pain in a primary care setting in respect to health-related quality of life (HRQoL) and work ability outcomes. The aim of this study was to evaluate the SBT’s predictive validity for HRQoL and work ability outcomes at long-term follow-up in a population with acute/subacute back and/or neck pain.SettingProspective data from 35 primary care centres in south Sweden during 2013.Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…This indicates that most participants remained at work despite LBP. This is in line with earlier studies (Chen et al., 2018 ; Forsbrand et al., 2018 ; Grovle et al., 2013 ). It could be argued that RTW might not be the right outcome measure for intervention studies where participants are working to some extent and that short‐term sick leave, for example, measured in days is more likely to detect change or between group differences, than measured in weeks.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that most participants remained at work despite LBP. This is in line with earlier studies (Chen et al., 2018 ; Forsbrand et al., 2018 ; Grovle et al., 2013 ). It could be argued that RTW might not be the right outcome measure for intervention studies where participants are working to some extent and that short‐term sick leave, for example, measured in days is more likely to detect change or between group differences, than measured in weeks.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, poor work ability combined with chronic disease is also associated with high risk for long-term sickness absence (29). Patients with LBP are also at risk for poor health-related quality of life (HRQoL) (39). In this study, those participants with poor FWA also had lower HRQoL.…”
Section: Discussionmentioning
confidence: 65%
“…SBST and work ability has also been associated with quality of life and daily life outcome in previous studies. 36 37 Patients' expectations of future work ability at 2 years, obtained at baseline, was associated with daily life outcome after 6 months in a German study of patients attending physiotherapy. 36 Also in line with our results, a Swedish group found that SBST could predict quality of life as well as work ability in patients with acute or subacute back or neck pain.…”
Section: Discussionmentioning
confidence: 99%
“…36 Also in line with our results, a Swedish group found that SBST could predict quality of life as well as work ability in patients with acute or subacute back or neck pain. 37 Our point of departure was that if screening tools integrate patients' perspective on the work dimension, it could facilitate and inform the integration of the work domain in management. The screening item from Örebro musculoskeletal pain questionnaire focused on patients' own expectations on future work ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation